Perilaku Pencarian Informasi pada Remaja Awal Mengenai Covid-19: Studi Kasus pada Remaja Awal Perumahan “X” - Fatimah, Fatimah (UI Scholars Hub, 2024)
This study discusses about the information seeking behavior on early teenagers regarding Covid-19, focusing on early teenagers in a housing cluster in West Java, Indonesia. This study aims to identify the information seeking behavior of the early teenagers in regards of fulfilling their information needs about Covid-19 amidst the Covid-19 pandemic using Ellis’ information seeking model. This study also aims to identify the sources of information and the challenges that teenagers are experiencing while doing the information seeking process. This study uses a qualitative approach with case study as its method. The data collection was done through observation and interviews that are done from March 2020 to May 2020. The result of this study shows that respondents are implementing Ellis’ information seeking model that are usually done through the process of starting, browsing, differentiating, monitoring, extracting, and ending. Within their information browsing process, the respondents would use search engines, social media, library application, and television as their media. The challenges experienced by the respondents vary from laziness in doing information seeking process, language barrier, and little knowledge about information seeking strategies.